Impact of Fieldwork on Students’ English Communication in Hospitality Services - Yahya, Muh; Rahmayanti, Firda; Widianto, Adita Taufik; Ridwan, Masri (LETS: Journal of Linguistics and English Teaching Studies, 2025)
Although English for Specific Purposes (ESP) is a key component of tourism education, limited research has examined how fieldwork experience impacts students’ English communication in real service settings. This study investigates the extent to which field practice improves English proficiency and service readiness among students at Makassar Tourism Polytechnic. Using a quantitative approach, data were gathered through questionnaires and analyzed using validity and reliability tests, a t-test, and R² analysis. Results show that fieldwork has a significant positive effect on students’ service readiness (t = 4.673; p = 0.001), with an R² value of 0.797 indicating that 79.7% of the variance is explained by field practice. The findings suggest that structured field experiences significantly enhance students’ English communication skills and professional competence. The study recommends integrating experiential and reflective learning into tourism curricula to better align academic training with industry needs.